Access to information and attitudes towards induced abortion: a community-based study among adults in the city of Colombo, Sri Lanka - Suchira Suranga; Kalinga Tudor Silva; Lakshman Senanayake (College of Community Physicians of Sri Lanka, 2017)
Introduction: Abortion is legally permitted in Sri Lanka, only if it is performed to save the mother's life. However, it is estimated that a large number of induced abortions takes place in Sri Lanka.   Objective: To describe the accessibility of abortion related information and its association with attitudes towards induced abortion in an urban community in Sri Lanka   Methods: A cross-sectional community-based household study was conducted in the City of Colombo among 743 respondents recruited using stratified, cluster sampling method. An interview-administered questionnaire collected data on access to formal and informal sources of information on induced abortion and attitudes on induced abortion and access to information on attitudes. Descriptive statistical analysis and non-parametric hypothesis testing were performed using SPSS software.   Results: The majority of respondents agreed to legalize abortion for rape (65%), incest (55%) and pregnancies with lethal foetal abnormalities (53%). However, less than 7% agreed to legalize induced abortion for other reasons such as contraceptive failure, bad economic condition and on request. The most common source of information on abortion was informal discussions, followed by the mass media. Access to information on abortion through newspapers, leaflets/handouts, television/ radio programs and news, internet and informal discussions shows a positive association with liberal attitudes towards induced abortion. Access to mass media showed the highest influence in determining abortion attitudes.   Conclusion: Access to information was positively associated with the liberal attitudes towards induced abortion.